Continuous Electrical Stimulation Affects Initial Growth and Proliferation of Adipose-Derived Stem Cells - Peer W. Kämmerer; Vivien Engel; Franz Plocksties; Anika Jonitz-Heincke; Dirk Timmermann; Nadja Engel; Bernhard Frerich; Rainer Bader; Daniel G. E. Thiem; Anna Skorska; Robert David; Bilal Al-Nawas; et al. (Biomedicines, 2020)
The aim of the study was to establish electrical stimulation parameters in order to improve cell growth and viability of human adipose-derived stem cells (hADSC) when compared to non-stimulated cells in vitro. hADSC were exposed to continuous electrical stimulation with 1.7 V AC/20 Hz. After 24, 72 h and 7 days, cell number, cellular surface coverage and cell proliferation were assessed. In addition, cell cycle analysis was carried out after 3 and 7 days. After 24 h, no significant alterations were observed for stimulated cells. At day 3, stimulated cells showed a 4.5-fold increase in cell numbers, a 2.7-fold increase in cellular surface coverage and a significantly increased proliferation. Via cell cycle analysis, a significant increase in the G2/M phase was monitored for stimulated cells. Contrastingly, after 7 days, the non-stimulated group exhibited a 11-fold increase in cell numbers and a 4-fold increase in cellular surface coverage as well as a significant increase in cell proliferation. Moreover, the stimulated cells displayed a shift to the G1 and sub-G1 phase, indicating for metabolic arrest and apoptosis initiation. In accordance, continuous electrical stimulation of hADSC led to a significantly increased cell growth and proliferation after 3 days. However, longer stimulation periods such as 7 days caused an opposite result indicating initiation of apoptosis.